Public expectation of local radio 1979 - Hedman, Lowe (Uppsala University, 1983)
The survey has been made at the request of the Committee for local radio, primarily to give information on expectations, knowledge and interest of the general public in local radio and general needs of information, and to gather such pieces of information about the public in the various test areas which could later on give explanations to eventual differences in the listening to the local radio, effects of local radio etc.

The survey has been made at the request of the Committee for local radio, primarily to give information on expectations, knowledge and interest of the general public in local radio and general needs of information, and to gather such pieces of information about the public in the various test areas which could later on give explanations to eventual differences in the listening to the local radio, effects of local radio etc.
Allmänhetens förväntningar på närradion 1979
Keywords: Media; Media; Social Sciences; Samhällsvetenskap